Mediating role of muscle quality in the liver–brain axis: integrated analysis of CT markers of body composition, brain aging, and biomarkers - Kim, Minchul; Pae, Chongwon; Moon, Joon Ho; Hwang, Inpyeong; Choi, Kyu Sung (Frontiers in Aging Neuroscience, 2025)
BackgroundThe liver, skeletal muscle, and brain are interconnected through metabolic and endocrine pathways, constituting a systemic axis that may influence neurodegeneration. Although hepatic steatosis and sarcopenia have been independently associated with neurodegeneration, their integrated effects on the brain remain poorly understood. This study investigated whether muscle density mediated the link between hepatic steatosis and neurodegeneration, quantified via the brain age gap (BAG).MethodsData from 2,510 adults (aged 22–87 years) who underwent abdominal computed tomography (CT), brain magnetic resonance imaging (MRI), and blood tests during comprehensive health evaluations were retrospectively analyzed. Fully automated CT markers, including visceral and subcutaneous fat, muscle, and the liver attenuation index (LAI) (a CT-based surrogate of hepatic steatosis) were obtained. The BAG was calculated from T1-weighted structural MRI scans using a pretrained machine learning pipeline. Mediation analysis was performed to evaluate the indirect effects of LAI on the BAG through muscle density. Network analysis further characterized the multivariate associations between the BAG, CT markers of body composition, laboratory results, and anthropometric variables.ResultsMediation analysis confirmed that muscle density, not muscle volume, partially mediated the LAI–BAG relationship (indirect β = −0.04, p < 0.001). LAI was negatively associated with the BAG (β = −0.027, p = 0.002) and positively associated with muscle density (β = 0.049, p < 0.001), whereas muscle density was inversely associated with BAG (β = −0.080, p < 0.001). Network analysis identified muscle density as a central hub linking the LAI, body composition, and the BAG. The BAG was also negatively correlated with Montreal Cognitive Assessment scores (r = −0.20, p < 0.001).ConclusionMuscle density mediates the effect of hepatic steatosis on brain aging, supporting its role as a key modifiable factor within the liver–brain axis. These findings underscore the importance of preserving muscle quality to decelerate brain aging.